PENINGKATAN KREATIVITAS BERWIRAUSAHA SISWA KELAS XII JASA BOGA 1 DALAM PENGOLAHAN LIMBAH BANDENG SEBAGAI PELUANG USAHA MELALUI UNIT PRODUKSI DI SMK NEGERI 3 PATI - Sri Puji Haryati (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The research aims are to: 1) increase students' creativity entrepreneurship Catering 1 Class XII in treating waste as a business opportunity thorns milkfish through the utilization of Production Unit of SMK Negeri 3 Pati and 2) determine the magnitude of the increase in Class XII student entrepreneurship creativity Catering 1 after using Production Unit of SMK Negeri 3 Pati. The method used is descriptive, the technique of classroom action research through qualitative and quantitative analysis. The pprinciples of recycling activity/procedures are: planning, acting, observing, and reflecting. Research held at SMK Negeri 3 Pati, with as many as 31 research subjects. Techniques of data collection are: observation, interviews, field notes, documentation. This study uses an interactive analysis that consists of data collection, data reduction, data presentation and conclusion. The research results showed that there is an increase in entrepreneurial creativity of each cycle, as seen in the first cycle the average value of creativity in entrepreneurship is 81% (the category of